Summer maize grain yield and soil carbon emission response to subsoiling before winter wheat sowing in the North China Plain. Issue 8 (3rd July 2023) - Zhang, Qingfen; Li, Ming; Shi, Ruilin; Zhang, Mingming; Han, Huifang; Li, Quanqi
ABSTRACT: Food security and carbon emissions are major challenges for China and the international community. To investigate the effects of different subsoiling depths on summer maize grain yield and soil carbon emissions, in 2016 and 2018, three tillage treatments, that is, rotary tillage at the depth of 15 cm (R15), subsoiling tillage at the depth of 40 cm (S40), and subsoiling tillage at the depth of 35 cm (S35), were set before winter wheat sowing. The effects of different tillage treatments on summer maize grain yield and soil carbon emissions were analyzed. The results showed that compared with R15, subsoiling increased the microbial biomass carbon in the 20–40 cm soil layers, and improved the soil respiration rate and CO2 -C cumulative emissions. The grain yield was increased by subsoiling, especially S35 (8.30% and 13.89% in 2018 and 2019, respectively). The carbon emission efficiency in S35 was significantly higher than that in S40. Altogether, we found that the best performance on grain yield of summer maize and carbon emission efficiency occurred in S35. S35 could be used to coordinate the relationship between summer maize grain yield and soil carbon emission. Therefore, this treatment can be applied and promoted in the NCP.